IMPLEMENTASI SISTEM MANAJEMEN MUTU PADA AGRIBISNIS KEDELAI LOKAL - Ridwan Iskandar (UNEJ e-Proceeding)
This study aimed to determine the level of implementation of quality management system on the agribusiness of local soybean in Banyuwangi and analyze the problems arising in the implementation of quality management as well as the alternative used to overcome the problem. Data from respondents were then processed and analyzed with a histogram, while the data comparison between the clause is processed with expert choice to determine the priority of implementation of the clause. Results from the study showed that the main priority of the application of quality management is a clause that called Focus On Customers with value weighting of 0.465, the next line is Improvement of Scale (0,256), Focus On Process (0.150), Organization (0.082) and Techniques (0.048). Based on management's assessment of the readiness of implementation, showed that the Technique clause is the lowest, so that the implementation of this clause should be improved.